PARADOKS ORANG MISKIN: KAJIAN SOSIOLOGIS ATAS CERPEN PERIHAL ORANG MISKIN YANG BAHAGIA KARYA AGUS NOOR - Doddy Kristianto (TELAGA BAHASA, 2018)
This article contains a discussion about the picture of the poverty of the main character in the short story About the Poor People by Agus Noor. The theory used in this research is the sociology of literature theory. The method used in this research is analytical descriptive method. The technique used in this study is literature review techniques. The results of the study are several factors that cause poverty of the main characters are (a) ignorance factors, (b) low motivational factors, (c) cultural factors of poverty, and (d) factors of misunderstanding of poverty. Meanwhile, the dominant attitude of beggar figures towards poverty that he experienced was (1) proud, (2) accepting the situation, (3) lazy, and (4) manipulative.